2016
DOI: 10.1101/lm.039537.115
|View full text |Cite
|
Sign up to set email alerts
|

Motivational state, reward value, and Pavlovian cues differentially affect skilled forelimb grasping in rats

Abstract: Motor skills represent high-precision movements performed at optimal speed and accuracy. Such motor skills are learned with practice over time. Besides practice, effects of motivation have also been shown to influence speed and accuracy of movements, suggesting that fast movements are performed to maximize gained reward over time as noted in previous studies. In rodents, skilled motor performance has been successfully modeled with the skilled grasping task, in which animals use their forepaw to grasp for sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 142 publications
(172 reference statements)
4
18
1
Order By: Relevance
“…This delayed separation suggests that at least in our experimental set-up, aspartame replacement does not facilitate learning trajectory. These findings are consistent with prior results indicating that reward palatability does not strongly influence learning in rodents (16).…”
Section: Resultssupporting
confidence: 93%
“…This delayed separation suggests that at least in our experimental set-up, aspartame replacement does not facilitate learning trajectory. These findings are consistent with prior results indicating that reward palatability does not strongly influence learning in rodents (16).…”
Section: Resultssupporting
confidence: 93%
“…We cannot 695 disentangle which of these two processes is more affected by motivation in our 696 paradigm. Although several studies have shown that the introduction of performance-697 contingent rewards also benefits the execution of motor skills (Mosberger et al, 2016;698 Wachter et al, 2009), the current results suggest that for implicitly trained skills that do 699 not allow for the pre-planning of movement this improvement is simply the result of a 700 global increase in movement speed and not skill-specific. 701…”
Section: Enhancement 624mentioning
confidence: 54%
“…As a 35 sequencing skill develops, these processes can be pre-planned, allowing for improved 36 performance (Ariani & Diedrichsen, 2019;Diedrichsen & Kornysheva, 2015). While 37 reward availability and increased motivation also improve performance of more complex 38 motor skills (Mosberger, De Clauser, Kasper, & Schwab, 2016;Wachter, Lungu, Liu, 39 Willingham, & Ashe, 2009), it remains unclear which stages of the motor planning 40 hierarchy from stimulus to movement (action selection, action execution, etc.) are 41 sensitive to these motivational effects.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the voluntary nature of the task extends the individual variation among the subjects, which may be utilized in detecting differences in learning capabilities. Since motor performance may be enhanced by increasing the motivation of the subjects (Mosberger et al 2016), we also planned to place food pellets on the pots as rewards for the successful jumps. However, it turned out later that the exploratory drive of the animals is enough for active participation in the task.…”
Section: Introductionmentioning
confidence: 99%